Crisis Politics and Austerity in the UK: Creative Instabilities?. (30th January 2017) - Gilbert, Jeremy
What has been the nature of capitalism's post-2008 crisis? This contribution argues its requirement for a creative dynamic population presents the greatest threat to capitalism's ability to reproduce continued inequality and undermine democracy. By mid 2015 a sense of severe 'organic crisis' (Gramsci's term) where ruling elites could be removed was not especially obvious outside Southern Europe (or in the UK outside Scotland) since capitalism's creative destruction may be considered inherently crisis-ridden. In this respect the decades old political settlement, consisting of ritualistic participation in a democracy that ensured a neoliberal programme will not be subject to any major revision or challenge, carried on unimpeded. Broad public consent for austerity measures in the UK was won off the back of a hysterical presentation of events in Greece. Cuts to public provision were cleverly and selectively directed at the weakest and most vulnerable underpinned by very traditional forms of legitimisation that of media demonization of these groups. The 'management of inequalities' (Maurizio Lazzarato's term) functioned successfully in the UK so as to prevent the framing of coherent alternatives or sets of democratic demands: this is why radical digital activism – despite setbacks – may yet prove to be important.